Generalized Difference Sequence Spaces with Ideal Convergence in n-Normed Spaces - Adhikari, Gobinda; Ghimire, Jhavi Lal (Nepal Journal of Mathematical Sciences, 2025)
In this paper, we define difference sequence spaces of type I-convergent, I-null, bounded I-convergent, and bounded I-null in n-normed space using the Orlicz function. We also study some algebraic and topological properties of these new sequence spaces including some inclusion relations.